1997
DOI: 10.1093/ps/76.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality and calcium availability from extruded and autoclaved turkey hatchery residue

Abstract: The protein quality of an extruded mixture of hatchery by-product meal and soybean meal (EHSM) and the calcium availability of autoclaved hatchery by-product meal (AHBM) were determined. In Experiments 1 and 2, EHSM or soybean meal (SBM) were the only protein sources in diets formulated to contain 16, 20, or 24% CP. In both experiments, there were five or six replicate pens randomly allotted to each level of dietary protein and each pen contained five poults. In Experiment 1, there was a significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…Some reports have been published on the performance of chickens when MBM was included in broiler diets (Martosiswoyo & Jensen, 1988;Baker & Firman, 1998;Weatherford & Cherry, 1999), but little if any on the inclusion of MBM in layer diets (Oruseibio, 1995). No negative effects were recorded with the inclusion of dietary MBM in turkey and broiler diets (Johri et al, 1980;Sell, 1996;Lilburn et al, 1997;Drewyor & Waldroup, 1998). In agreement with our results, Damron et al (2001) reported that the inclusion of MBM up to a level of 6.0% had no negative effect on laying hen performance.…”
Section: Resultssupporting
confidence: 90%
“…Some reports have been published on the performance of chickens when MBM was included in broiler diets (Martosiswoyo & Jensen, 1988;Baker & Firman, 1998;Weatherford & Cherry, 1999), but little if any on the inclusion of MBM in layer diets (Oruseibio, 1995). No negative effects were recorded with the inclusion of dietary MBM in turkey and broiler diets (Johri et al, 1980;Sell, 1996;Lilburn et al, 1997;Drewyor & Waldroup, 1998). In agreement with our results, Damron et al (2001) reported that the inclusion of MBM up to a level of 6.0% had no negative effect on laying hen performance.…”
Section: Resultssupporting
confidence: 90%
“…Said [28] reported that dry extrusion was an effective method to treat hatchery waste. For example Miller [29] extruded a mixture of ground hatchery waste and yellow maize meal (25:75) at 140 C for 10 s, while Lilburn et al [30] autoclaved turkey hatchery waste for 15 min at 125 C and 1.76 kg/cm 2 and then dried it at 50 C for 1 hour. Similarly Verma and Rao [31] autoclaved hatchery waste (infertile eggs or eggs with dead embryos) and dried it at 100 C for 10 h. Ravindra-Reddy and Rajasekhar-Reddy [32] autoclaved day old cull male chicks for 30 min.…”
Section: Outoclaved and Extrudedmentioning
confidence: 99%
“…crude protein (33.1%), fat (29%), crude fiber (12.1%), AME (23.9 MJ/kg), calcium (25.62%) and phosphorus (1.47%) (Lilburn et al 1997;Mehdipour et al 2009). Protein from hatchery waste flour have high biological value, a good balance of amino acids, as well as more competitive prices compared to soybean and fish meal (Lilburn et al 1997;Shahriar et al 2008). Our previous experiments noted that the nutritional content of the hatchery waste that consisting of eggs shell, infertile eggs, un-hatched eggs, and the culled DOC have a water content of ±60%, crude protein ±20% and crude lipid ±9%.…”
Section: Introductionmentioning
confidence: 99%